Congenital Heart Disease - Harun Alrasyid; Suhadi Suhadi; Sutaryo Sutaryo; Rosyid Ridho; A. Samik Wahab; Ismangoen Ismangoen (Indonesian Pediatric Society, 1980)
This paper reports 54 cases of congenital heart disease which were diagnosed by simple methods, without cathetherisation and Angiocardiography. These consisted of : 1). 37% Ventricular septal defect. 2). 24% Atrial Septal defect, second type. 3). 11,11% Patent Ductus Arteriosus Botalli. 4). 9% Tetralogy of Fallot. 5). 7,5% Stenosis pulmonalis. 6). 3,7% Atrial septal defect primary type. 7). 1,85% Aorta stenosis. 8). 2% Others. Early signs and symptoms were: frequent cough, growth retardation, dyspnoe d'effort, Electrocardiographic and Rontgenologic abnormalities. With simple examinations we can almost accurately diagnose congenital heart disease. We suggest to build up more cardiac centres to overcome congenital heart disease problems.